(untitled) (Italian Journal of Public Health, 2011)
The discovery of penicillin is associated with the name of Alexander Fleming, who in 1928 demonstrated the inhibition of growth of a bacterium around a mold, Penicillium notatum, on a culture plate. In 1940, based on the studies of Fleming, Florey and Chain were able to isolate and produce penicillin. Penicillin was to become a precious resource for the many wounded soldiers during the Second World War, paving the way for a new era in medicine. Fleming, Florey and Chain were awarded the Nobel Prize for Medicine in 1945 for the discovery of penicillin and its curative effects. However, in the official history of the discovery of penicillin there is a page that is missing: the page of Vincenzo Tiberio.